A temperature-driven catalytic hydrogen peroxide generation core-shell composite and a preparation method thereof
Patent Information
- Application Number
- CN202611181845.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]本发明旨在提供一种温度驱动催化生成过氧化氢的核壳复合材料及其制备方法,以解决现有H2O2生成体系依赖化学或光学刺激、响应不可控的问题
(1)利用天然海泡石为硅源,在无需引入其他有机硅源的条件下,能够直接通过模板法将提取的硅源组装成为介孔MCM-41。
Smart Images

Figure CN122999284A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of natural non-metallic mineral processing and functional catalytic materials technology, specifically to a core-shell composite material for temperature-driven catalytic generation of hydrogen peroxide and its preparation method. Background Technology
[0002] Hydrogen peroxide (H2O2) is a green chemical with strong oxidizing properties, widely used in medical disinfection, food sterilization, wastewater treatment, and air purification. Its sterilization mechanism primarily relies on the strong oxidizing effect of hydroxyl radicals (·OH), which effectively disrupt the cell membrane structure and metabolic system of microorganisms, offering advantages such as high efficiency, no residue, and environmental friendliness. Therefore, hydrogen peroxide has extremely high application value in public health control, medical device sterilization, and environmental remediation. Currently, the industrial production of H2O2 mainly uses the anthraquinone process. Although this process is mature, it suffers from problems such as complex procedures, toxic raw materials, high energy consumption, and severe pollution, hindering the development of the green sterilization and disinfection industry.
[0003] In recent years, researchers have attempted to achieve in-situ preparation of H2O2 through catalytic methods to meet the needs of on-site sterilization and environmental remediation. Among these, "temperature-driven" catalysis technology is considered a promising route for future H2O2 preparation due to its independence from power sources or light sources, its ability to utilize changes in ambient temperature to drive the reaction, and its simple and controllable apparatus. Metal-organic frameworks (MOFs) exhibit unique advantages in thermocatalytic oxidation reactions due to their highly ordered microporous structures and abundant tunable coordination sites. ZIF-8, as a typical MOF material, possesses a high specific surface area, controllable pore size, and excellent chemical stability. Its Zn–N coordination centers can promote oxygen activation and electron transfer, thus exhibiting certain activity in the thermocatalytic preparation of H2O2. However, ZIF-8 alone is prone to structural collapse under high-temperature conditions, and its microporous structure restricts the diffusion of reactant molecules, affecting thermocatalytic efficiency.
[0004] Therefore, introducing a support material with high thermal stability and an ordered mesoporous structure has become an optimization strategy. MCM-41 is a typical mesoporous silica material with a regular hexagonal pore arrangement, high specific surface area, and good thermochemical stability. Its open mesoporous structure can effectively improve the diffusion and mass transfer of reactant molecules in the catalytic system. By combining ZIF-8 with MCM-41, a microporous-mesoporous synergistic core-shell structure system can be constructed, which combines high activity and high stability, and is expected to achieve efficient thermocatalytic generation of H2O2.
[0005] Furthermore, using natural sepiolite as the silicon source to prepare MCM-41 can significantly reduce costs and improve sustainability. It also leverages the abundant Si–O–Mg structure in sepiolite to promote the nucleation of the MCM-41 framework. Introducing active functional groups onto the MCM-41 surface provides chemical anchoring sites for ZIF-8, enhancing the stability of the core-shell interface. This strategy helps construct novel core-shell composite catalytic materials with both high thermal stability and high catalytic activity, providing an efficient and green technical route for the thermocatalytic preparation of H2O2 for sterilization. Summary of the Invention
[0006] The present invention aims to provide a core-shell composite material for temperature-driven catalytic generation of hydrogen peroxide and its preparation method, in order to solve the problems of existing H2O2 generation systems that rely on chemical or optical stimulation and have uncontrollable responses.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solution: a core-shell ZIF-8@MCM-41 composite material for temperature-driven thermocatalytic H2O2 generation. The acid leaching-surface modification-template process used provides an effective and universal method for preparing ZIF-8@MCM-41 core-shell structures with high interfacial stability. In addition, the proposed temperature-driven catalytic H2O2 generation has important guiding significance for achieving efficient and green bactericidal performance in the future.
[0008] This invention proposes a high specific surface area mesoporous MCM-41 and its preparation method. The mesoporous MCM-41 is prepared by acid leaching-templating method using sepiolite, a natural clay mineral, as a silicon source for structural recombination. By controlling the concentration of the template agent hexadecyltrimethylammonium bromide (CTAB), MCM-41 materials with different pore sizes can be obtained. The pore size of the prepared samples is mainly distributed in the mesoporous range, with a pore size of 2.83 nm and a specific surface area of 10¹⁶ m². 2 g -1 The specific preparation steps include: (1) The sepiolite was thoroughly dispersed and mixed with 8 mol / L HCl at a ratio of 1 g / 10 ml, and then reacted at 80 °C for 2 h. After the reaction was completed, the sepiolite was centrifuged and washed at 5000 rpm / min until neutral to obtain the solid product acid-etched sepiolite, and then dried at 60 °C for 24 h.
[0009] (2) Add the solid product obtained in step (1) to 20 ml of 0.1 mol / L LTAB solution, stir and mix evenly, adjust the pH of the system to 12 using 0.5 mol / L NaOH solution, and react at 60℃ for 2 h.
[0010] (3) The reaction mixture obtained in step (2) was directly transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 100°C for 24 h to obtain a solid product. After drying the product at 60°C for 24 h, it was calcined at 540°C for 6 h to remove the template agent, and finally a high specific surface area, monodisperse mesoporous MCM-41 material was obtained.
[0011] This invention also provides a surface-modified MCM-41 material and its preparation method. The method modifies the surface of MCM-41 by using the synergistic effect of the silane coupling agent APTES and succinic anhydride, introducing carboxyl (-COOH) functional groups onto its surface, thereby significantly enhancing the binding ability of MCM-41 to ZIF-8 and improving its surface activity. Specific steps include: (1) In a 60 mL LMF solution, slowly add 5 mL LAPTES solution. After mixing evenly, continue to add 2.5 g succinic anhydride. After the succinic anhydride is completely dissolved, keep the mixture at 40 °C and stir continuously for 5 h.
[0012] (2) Weigh 1g of MCM-41 powder, add it to 30ml of LDM solution, and disperse it evenly by ultrasonic dispersion to obtain a uniform suspension. Slowly drop the suspension into the mixture in step (1), and continue stirring for 6h. After the reaction is completed, centrifuge at 5000rpm / min to neutralize and dry at 60℃ for 12h.
[0013] Finally, this invention provides an application of the core-shell structure ZIF-8@MCM-41 with temperature-driven thermocatalytic hydrogen peroxide generation and its preparation method. The specific synthesis steps of the material are as follows: the modified MCM-41 is thoroughly mixed with a methanol solution of zinc nitrate hexahydrate and kept under sonication for 5 minutes. Then, a methanol solution of 2-methylimidazole is added, and after mixing evenly, the mixture is reacted at room temperature for 1.5 hours. After centrifugation, the mixture is vacuum dried at 60°C for 12 hours.
[0014] It has the following beneficial effects: (1) Using natural sepiolite as a silicon source, the extracted silicon source can be directly assembled into mesoporous MCM-41 by template method without the need to introduce other organosilicon sources.
[0015] (2) The ZIF-8 shell has a highly ordered microporous structure and abundant active sites. Its Zn–N coordination center can efficiently adsorb and activate oxygen molecules, promote the electron transfer reaction between oxygen and water, and thus achieve efficient generation of H2O2 under temperature-driven conditions.
[0016] (3) The mesoporous structure of MCM-41 helps the mass transfer of reactants and products, improves the efficiency of catalytic reaction, and provides high thermal stability. The pore structure of MCM-41 can not only enhance the specific surface area of the catalyst, but also improve the stability of the catalyst at high temperature. Attached Figure Description
[0017] Figure 1 SEM image of natural sepiolite; Figure 2 SEM image of the mesoporous MCM-41 prepared in Example 1; Figure 3 A comparison of N2 adsorption-desorption curves of modified mesoporous MCM-41 and sepiolite prepared in Example 1; Figure 4 The FTIR spectrum of the modified MCM-41 prepared in Example 4; Figure 5 TEM image of ZIF-8@MCM-41 prepared in Example 5; Figure 6 TEM image of N-ZIF-8@MCM-41 prepared in Comparative Example 1; Figure 7 This is a comparison chart of hydrogen peroxide generation of ZIF-8@MCM-41 prepared in Example 6 as a function of temperature. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] This invention provides a high specific surface area mesoporous MCM-41 and its preparation method. The mesoporous MCM-41 is prepared by acid leaching-template method using natural clay as a silicon source for structural recombination. See [link to relevant documentation]. Figure 1 and Figure 2 Natural sepiolite exhibits a typical fibrous structure with fiber lengths of 1-2 μm. After synthesis via an acid etching-template method, the Mg-OH octahedral structure in the natural clay component can be removed, and the resulting mesoporous MCM-41 molecular sieve with high porosity can be obtained through reassembly. As shown in Table 1, the obtained MCM-41 has a pore size of 2.83 nm and a specific surface area of 10¹⁶ m². 2 ∙g -1 The specific preparation steps include: (1) Natural clay and HCl were thoroughly dispersed and mixed at a ratio of 1g / 10ml, and then reacted at 80℃ for 2h. After the reaction was completed, the mixture was centrifuged and washed at 5000rpm / min until neutral to obtain the acid-etched sepiolite solid product, which was then dried at 60℃ for 24h.
[0020] (2) Add the solid product obtained in step (1) to 20 ml of surfactant solution, stir and mix evenly, adjust the pH value of the system with NaOH solution, and react at 60℃ for 2 h.
[0021] (3) The reaction mixture obtained in step (2) is directly transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 100°C for 24 hours to obtain a solid product. After drying the product at 60°C for 24 hours, it is calcined at 540°C for 6 hours to remove the template agent and finally obtain a high specific surface area, monodisperse mesoporous MCM-41 material.
[0022] In one specific embodiment, the natural clay is sepiolite, a natural hydrous magnesium silicate mineral. The framework of sepiolite consists of alternating continuous Si–O–Si layers and Mg–O octahedral chains, rich in soluble Mg–O–Si bonds and surface hydroxyl groups. This provides an ideal chemical basis for the controllable dissolution and reconstruction of the silicon source. Acid etching can effectively remove the magnesium layers, simultaneously inducing the transformation of the structure from ordered layers to amorphous SiO2, thereby obtaining a highly active silicon source precursor. This provides a uniform silicon source for the subsequent formation of MCM-41. Furthermore, compared to traditional silicon sources (such as TEOS or silica sol), sepiolite is widely available, inexpensive, and environmentally friendly, enabling high-value utilization of mineral resources. More importantly, the natural fibrous morphology of sepiolite can serve as a structural guide or morphology control template during the formation of MCM-41, resulting in a material with a higher specific surface area, more uniform pore size distribution, and excellent structural stability.
[0023] In one specific embodiment, the concentration of HCl is chosen to be 8 mol / L, which can selectively remove Mg. 2+ Fe 2+ Soluble cations are introduced, which simultaneously disrupt some of the layer chain connection structures, reducing the crystallinity of the material and increasing the proportion of amorphous SiO2 phase. This significantly enhances the reactivity and specific surface area of the silicon source, effectively removing metal impurities, increasing specific surface area and porosity, while preserving the morphology and partial skeletal order of sepiolite fibers, providing an ideal precursor for the uniform growth and stable morphology of MCM-41.
[0024] In one specific embodiment, the surfactant is hexadecyltrimethylammonium bromide (CTAB) at a concentration of 0.1 mol / L. CTAB is a typical cationic surfactant whose molecules consist of a positively charged quaternary ammonium head group and a long-chain alkyl tail group. CTAB molecules self-assemble to form spherical or rod-shaped micelle structures. These ordered micelles can interact with the silicon source in an alkaline medium through electrostatic interactions and hydrogen bonding, inducing the gradual deposition and condensation of the silicon-oxygen framework on the micelle surface, thereby forming a regular hexagonal mesoporous structure MCM-41.
[0025] In one specific embodiment, the concentration of NaOH was chosen to be 0.5 mol / L, and the pH was adjusted to 12. The pH environment of 12 is conducive to the stable existence and orderly arrangement of CTAB micelles, promotes the directional deposition and assembly of Si–O tetrahedra at the micelle interface, and can also effectively inhibit the premature polymerization or gelation of silicon species, ensuring that the polycondensation process is carried out in a controlled manner, thereby obtaining MCM-41 material with uniform pore size distribution, high specific surface area and regular structure.
[0026] This invention also provides a surface-modified MCM-41 material and its preparation method. The method modifies the surface of MCM-41 by using the synergistic effect of a silane coupling agent and an anhydride to introduce carboxyl (-COOH) functional groups on its surface, thereby significantly enhancing the binding ability of MCM-41 with ZIF-8 and improving its surface activity. The specific preparation steps include: adding the coupling agent and anhydride to a beaker containing a DMF solution, stirring evenly, and reacting at 40°C for 5 hours. Then, adding a DMF suspension of MCM-41 and continuing the reaction for 6 hours, centrifuging and washing, and drying at 60°C for 12 hours to obtain modified MCM-41.
[0027] In one specific embodiment, 3-aminopropyltriethoxysilane (APTES) and succinic anhydride were used to synergistically modify MCM-41. The mass ratio of MCM-41, 3-aminopropyltriethoxysilane, and succinic anhydride was 1:4.8:2.5. Through bifunctionalization of amino and carboxyl groups, the surface of MCM-41 can interact with Zn in ZIF-8. 2+ Alternatively, imidazole ligands can form a stable chemical anchor, improving the strength of the core-shell interface binding and structural stability.
[0028] Finally, this invention provides an application of the core-shell structure ZIF-8@MCM-41 with temperature-driven thermocatalytic H2O2 generation and its preparation method. The specific synthesis steps of the material are as follows: Modified MCM-41 is thoroughly mixed with a methanol solution of zinc nitrate hexahydrate and kept under sonication for 5 minutes. Then, a methanol solution of 2-methylimidazole is added, mixed evenly, and reacted at room temperature for 1.5 hours. The mixture is then centrifuged and vacuum dried at 60°C for 12 hours.
[0029] In one specific embodiment, the mass ratio of modified MCM-41, zinc nitrate hexahydrate, and 2-methylimidazole is 0.5:2:3.5, the concentration of the methanol solution of zinc nitrate hexahydrate is 2 g / 30 ml, and the concentration of the methanol solution of 2-methylimidazole is 3.5 g / 30 ml.
[0030] Example 1:
[0031] Prepare 250 ml of HCl solution with a concentration of 8 mol / L.
[0032] (1) Add 2.5g of sepiolite to HCl solution, mix it uniformly by ultrasound, and then react at 80℃ for 2h. After the reaction is completed, wash it by centrifugation at 5000rpm / min until neutral to obtain a solid product, and dry it at 60℃ for 24h.
[0033] (2) Prepare 20 ml of 0.1 mol / L LTAB solution, take 0.4 g of the solid sample obtained in step (1) and add it to the above solution and mix thoroughly. Adjust the pH to 12 using 0.5 mol / L NaOH solution, and then react at 60°C for 2 h.
[0034] (3) The reaction product obtained in step (3) is directly transferred to a high-pressure reactor with a polytetrafluoroethylene liner. After reacting at 100°C for 24 hours, the product is washed by centrifugation at 5000 rpm / min until it becomes neutral to obtain a solid product. The product is then dried at 60°C for 24 hours and calcined at 540°C at a rate of 2°C / min for 6 hours.
[0035] (4) The obtained solid product is finely ground with an agate mortar and passed through a 200-mesh sieve to produce monodisperse mesoporous MCM-41 with high specific surface area.
[0036] Examples 2-3:
[0037] Following the method in Example 1, CTAB solutions with molar ratios of 0.05 and 0.15 mol / L were used as template agents, and other conditions remained unchanged. The specific surface area data of the prepared MCM-41 are shown in Table 1.
[0038] Example 4:
[0039] (1) Add 5 ml of APTES solution to 60 ml of DMF solution, mix well, and then add 2.5 g of succinic anhydride. After the mixture is fully dissolved, stir it continuously at 40 °C for 5 h.
[0040] (2) Weigh 1g of MCM-41 powder and mix it into another 30ml DMF solution. After ultrasonic dispersion, a uniform suspension is obtained. Then, the suspension is slowly poured into the mixture in step (1) and the reaction continues for 6h. The product is centrifuged and washed at 5000rpm / min until neutral and dried at 60℃ for 12h.
[0041] Example 5:
[0042] (1) Add 2g of zinc nitrate hexahydrate to 30ml of anhydrous methanol and dissolve it completely. Then add 0.5g of modified MCM-41 to the solution, mix well, and place it in an ultrasonic bath for 5min to allow Zn to react. 2+ Pre-coordinated with modified MCM-41.
[0043] (2) Weigh out 3.5g of 2-methylimidazole and dissolve it in another 30ml of anhydrous methanol. Then, pour the 2-methylimidazole solution into the mixture in step (1) with rapid stirring and continue to stir rapidly at room temperature for 1.5h.
[0044] (3) After the reaction, the sample was repeatedly washed with methanol to remove residual zinc nitrate hexahydrate and 2-methylimidazole. Finally, it was vacuum dried at 60°C for 12 h to obtain ZIF-8@MCM-41 core-shell material.
[0045] Comparative Example 1: Without modifying MCM-41, the remaining raw materials and steps were exactly the same as in Example 5, and the resulting composite material was named N-ZIF-8@MCM-41.
[0046] Test Example 1: SEM observations of sepiolite and MCM-41 were performed separately, and the results are as follows: Figure 1 and 2 .
[0047] Results analysis: Natural sepiolite exhibits a typical fibrous structure with fiber lengths of 1-2 μm. After synthesis via acid etching-template method, the Mg-O octahedral structure in the natural clay component is removed, transforming it into MCM-41 material with an amorphous structure and a size of approximately 1-5 μm.
[0048] Test Example 2: N2 adsorption-desorption curves were tested for sepiolite and MCM-41, and the results are as follows: Figure 3 .
[0049] Results analysis: From Figure 3As shown in Table 1, natural sepiolite exhibits a typical Type IV isotherm with a distinct H3 hysteresis loop, indicating that its pore structure is mainly composed of irregular mesoporous channels formed by interfiber stacking. In contrast, the synthesized MCM-41 exhibits a typical Type IV isotherm with an H1 hysteresis loop and a steep capillary condensation step, indicating that it has a regular and uniform hexagonal mesoporous arrangement. Table 1 shows that the pore size of sepiolite is 3.4 nm and its specific surface area is 296 m². 2 ∙g -1 The MCM-41 has a pore size of 2.83 nm and a specific surface area of 10¹⁶ m². 2 ∙g -1。 Table 1. Pore size analysis data of sepiolite and MCM-41 SEP 296 3.4 0.5 MCM-41 1016 2.83 0.91 Test Example 3: FTIR tests were performed on MCM-41 and modified MCM-4 respectively, and the results are as follows: Figure 4 .
[0050] Results analysis: The FTIR spectra of both unmodified MCM-41 and APTES-succinic anhydride co-modified MCM-41 exhibited typical characteristic peaks of a mesoporous silica framework, with the peak at approximately 1077 cm⁻¹ being the most prominent. -1 The Si-O-Si asymmetric stretching vibration peak at approximately 802 cm⁻¹ -1 Symmetric stretching vibration peak and approximately 457 cm -1 The bending vibration peak indicates that the mesoporous structure of the material remains intact after modification. Compared with the original sample, a new absorption peak appears at 2935 cm⁻¹ in the modified sample, corresponding to the CH stretching vibration of the -CH₂ group in the APTES molecule, indicating that the organosilane has been successfully grafted onto the MCM-41 surface. Meanwhile, the peak at 1714 cm⁻¹... -1 The distinct absorption peak at approximately 3445 cm⁻¹ is attributed to the C=O stretching vibration of the succinic anhydride-derived carboxyl group, indicating a ring-opening reaction between succinic anhydride and the amino group in APTES. -1 The broad OH / NH stretching vibration band further confirms the introduction of amino and carboxyl functional groups.
[0051] Test Example 4: TEM electron microscopy was performed on ZIF-8@MCM-41 and N-ZIF-8@MCM-41, and the results are as follows: Figure 5 and Figure 6 .
[0052] Results analysis: From Figure 4 and Figure 5As can be seen, the unmodified MCM-41 surface lacks sufficient chemical anchoring sites, resulting in uneven nucleation of ZIF-8 crystals on its surface. ZIF-8 grains are mostly distributed in an isolated state on the MCM-41 surface, with obvious exposed core layers in some local areas. In contrast, the bifunctional modified MCM-41 sample exhibits a typical dense core-shell structure in TEM. The core-shell interface boundary is clear, with a thickness of approximately 100-200 nm. These results demonstrate that APTES-succinic anhydride modification of the MCM-41 surface can effectively promote uniform epitaxial coating and interface strengthening of ZIF-8, which is a key step in achieving highly stable and highly active ZIF-8@MCM-41 core-shell composite materials.
[0053] Test Example 5: The hydrogen peroxide production of ZIF-8@MCM-41 at different temperatures was tested using UV-Vis spectrophotometry, and the results are as follows: Figure 7 .
[0054] Results analysis: ZIF-8@MCM-41 exhibits significant temperature difference response characteristics, from Figure 7 It can be seen that the material generates hydrogen peroxide during both heating (25→35℃) and cooling (25→15℃), indicating that its generation process is sensitive to temperature changes. The amount of hydrogen peroxide generated during heating is significantly higher than that during cooling. This may be because heating increases molecular motion energy, accelerates the reaction rate and product diffusion, thus resulting in a higher generation amount. Therefore, ZIF-8@MCM-41 can be considered to have temperature-driven catalytic characteristics.
[0055] Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art and related fields based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention. Structures, devices, and operating methods not specifically described and explained in the present invention, unless otherwise specified or limited, shall be implemented according to conventional means in the art.
Claims
1. A core-shell composite material for temperature-driven catalytic generation of hydrogen peroxide, characterized in that, The structure is ZIF-8@MCM-41, consisting of a modified MCM-41 core and a ZIF-8 shell, with a pore size of 3.95 nm and a specific surface area of 808 m². 2 ∙g -1 .
2. The core-shell composite material for temperature-driven catalytic generation of hydrogen peroxide according to claim 1, characterized in that, Hydrogen peroxide can be generated under temperature-driven conditions.
3. The core-shell composite material for temperature-driven catalytic generation of hydrogen peroxide according to claim 2, characterized in that, The MCM-41 was synthesized from natural clay minerals as the silicon source via an acid leaching-template method. The pore size of the prepared sample was mainly distributed in the mesoporous range, with an average pore size of 2.83 nm and a specific surface area of 10¹⁶ m². 2 ∙g -1 .
4. The method for preparing a core-shell composite material for temperature-driven catalytic hydrogen peroxide generation according to claim 3, characterized in that, The preparation steps include: S1. Natural clay and HCl were thoroughly mixed at a ratio of 1g / 10ml, and then reacted at 80℃ for 2h. After the reaction was completed, the mixture was centrifuged and washed at 5000rpm / min until neutral to obtain the solid product, acid-etched sepiolite, which was then dried at 60℃ for 24h. S2. After preparing the surfactant solution, add the solid product obtained in step S1, stir and mix evenly, adjust the pH value of the system with NaOH solution, and react at 60℃ for 2 hours. S3. The reaction mixture obtained in step S2 is directly transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 100°C for 24 hours to obtain a solid product. After drying the product at 60°C for 24 hours, it is calcined at 540°C for 6 hours to remove the template agent, and finally a high specific surface area, monodisperse mesoporous MCM-41 material is obtained. S4. Add coupling agent and acid anhydride to a beaker containing DMF solution, stir evenly and react at 40℃ for 5h, then add the DMF suspension of MCM-41 obtained in step S3 and continue to react for 6h, centrifuge and wash, dry at 60℃ for 12h to obtain modified MCM-41. S5. The modified MCM-41 was thoroughly mixed with a methanol solution of zinc nitrate hexahydrate and kept under sonication for 5 minutes. Then, a methanol solution of 2-methylimidazole was added, and the mixture was mixed evenly. The mixture was reacted at room temperature for 1.5 hours, centrifuged, and dried under vacuum at 60°C for 12 hours to obtain ZIF-8@MCM-41.
5. The method for preparing a core-shell composite material for temperature-driven catalytic hydrogen peroxide generation according to claim 4, characterized in that, The natural clay is sepiolite, with a SiO2 content of 70wt%, a MgO content of 26wt%, an Al2O3 content of 2wt%, and Fe2O3 and CaO contents of 0.8wt% and 0.5wt%, respectively.
6. The method for preparing a core-shell composite material for temperature-driven catalytic hydrogen peroxide generation according to claim 4, characterized in that, The surfactant is hexadecyltrimethylammonium bromide with a concentration of 0.1 mol / L, the HCl concentration is 8 mol / L, and the NaOH concentration is 0.5 mol / L. The NaOH is used to adjust the pH value to 12.
7. The method for preparing a core-shell composite material for temperature-driven catalytic hydrogen peroxide generation according to claim 4, characterized in that, The ratio of the acid-leached sepiolite to the hexadecyltrimethylammonium bromide solution is 0.4 g / 20 ml.
8. The method for preparing a core-shell composite material for temperature-driven catalytic hydrogen peroxide generation according to claim 4, characterized in that, The silane coupling agent is 3-aminopropyltriethoxysilane, and the acid anhydride is succinic anhydride, wherein the mass ratio of MCM-41, 3-aminopropyltriethoxysilane and succinic anhydride is 1:4.8:2.
5.
9. A method for preparing a core-shell composite material for temperature-driven catalytic hydrogen peroxide generation according to claim 4, characterized in that, The thickness of the ZIF-8 outer shell in the prepared ZIF-8@MCM-41 is 100–200 nm.
10. A method for preparing a core-shell composite material for temperature-driven catalytic hydrogen peroxide generation according to claim 4, characterized in that, The mass ratio of the modified MCM-41, zinc nitrate hexahydrate, and 2-methylimidazole is 0.5:2:3.5, the concentration of the methanol solution of zinc nitrate hexahydrate is 2 g / 30 ml, and the concentration of the methanol solution of 2-methylimidazole is 3.5 g / 30 ml.
